Genome-wide association study meta-analysis of chronic widespread pain: evidence for involvement of the 5p15.2 region. Issue 3 (6th September 2012) - Peters, Marjolein J; Broer, Linda; Willemen, Hanneke L D M; Eiriksdottir, Gudny; Hocking, Lynne J; Holliday, Kate L; Horan, Michael A; Meulenbelt, Ingrid; Neogi, Tuhina; Popham, Maria; Schmidt, Carsten O; Soni, Anushka; et al.
Abstract : Background and objectives: Chronic widespread pain (CWP) is a common disorder affecting ∼10% of the general population and has an estimated heritability of 48–52%. In the first large-scale genome-wide association study (GWAS) meta-analysis, we aimed to identify common genetic variants associated with CWP. Methods: We conducted a GWAS meta-analysis in 1308 female CWP cases and 5791 controls of European descent, and replicated the effects of the genetic variants with suggestive evidence for association in 1480 CWP cases and 7989 controls. Subsequently, we studied gene expression levels of the nearest genes in two chronic inflammatory pain mouse models, and examined 92 genetic variants previously described associated with pain. Results: The minor C-allele of rs13361160 on chromosome 5p15.2, located upstream of chaperonin-containing-TCP1-complex-5 gene (CCT5) and downstream of FAM173B, was found to be associated with a 30% higher risk of CWP (minor allele frequency=43%; OR=1.30, 95% CI 1.19 to 1.42, p=1.2×10 −8 ). Combined with the replication, we observed a slightly attenuated OR of 1.17 (95% CI 1.10 to 1.24, p=4.7×10 −7 ) with moderate heterogeneity (I2=28.4%). However, in a sensitivity analysis that only allowed studies with joint-specific pain, the combined association was genome-wide significant (OR=1.23, 95% CI 1.14 to 1.32, p=3.4×10 −8, I2=0%). Expression levels of Cct5 and Fam173b in mice with inflammatory pain were higher in the lumbar spinal cord, not in the lumbar dorsal root ganglions, compared to mice without pain. None of the 92 genetic variants previously described were significantly associated with pain (p>7.7×10 −4 ). Conclusions: We identified a common genetic variant on chromosome 5p15.2 associated with joint-specific CWP in humans. This work suggests that CCT5 and FAM173B are promising targets in the regulation of pain.